2014
DOI: 10.1074/jbc.m114.583286
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Substrate Specificity of a Eukaryotic Fucosidase from Fusarium graminearum

Abstract: Background: Fucosidase releases terminal fucose from functionally diverse glycans. Results: The first eukaryotic fucosidase crystal structures reveal two active-site conformations and a novel ␤␥-crystallin domain. Conclusion: Catalytically essential glutamate in glycoside hydrolase family 29 (GH29) fucosidases is structurally conserved despite locally poor sequence conservation. Significance: Conformational flexibility involving the general acid/base Glu exists in GH29 fucosidases across different life domains. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
50
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(56 citation statements)
references
References 83 publications
6
50
0
Order By: Relevance
“…The protein sequence alignment predicted that D206 was the catalytic nucleophile in B. xylophilus ; the prediction was confirmed with structure analysis. The D206 is located at the same position as the catalytic nucleophile aspartate residue found in bacteria and fungus . Among two predicted acid/base residues E55 and E270 from sequence alignment, structurally E270 shares the same position as the catalytic acid/base glutamate residue in F. graminearum , but a hydrogen bond was found between E55 and fucose.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The protein sequence alignment predicted that D206 was the catalytic nucleophile in B. xylophilus ; the prediction was confirmed with structure analysis. The D206 is located at the same position as the catalytic nucleophile aspartate residue found in bacteria and fungus . Among two predicted acid/base residues E55 and E270 from sequence alignment, structurally E270 shares the same position as the catalytic acid/base glutamate residue in F. graminearum , but a hydrogen bond was found between E55 and fucose.…”
Section: Discussionmentioning
confidence: 99%
“…45 -L-fucosidase from the plant pathogenic fungus F. graminearum was found actively hydrolyzing the fucose from xyloglucan. 17 Pinus pinea is rich in -1,3-linked fucose and Lewis A N-glycans with fucose residue, 46 and fucose is also found in the xyloglucans, which is the major hemicellulosic matrix polysaccharides in the cell wall of pine. 47,48 It is likely that the Bxy-FUCA may act as a digestive enzyme in the intestine of B. xylophilus, and defucosylate the side groups and expose the hemicellulose backbone for further digestion.…”
Section: Bxy-fuca Is Mainly Expressed In Bwm and Intestine Throughoutmentioning
confidence: 99%
“…S11), which is surprising since these highly sulfated polymers are found mostly in the cell wall matrix of brown algae (10). The putative fucoidanases in these genotypes have sequence similarities of 30-40% to the enzyme from Fusarium graminearum (AFR68935), which has been suggested to play a role in plant pathogenesis (45). This enzyme shows preference toward α-1,2-linked fucosyl substrates rather than fucan containing α-1,3 (4) linkages as reported for other GH29 fucosidases.…”
Section: Resultsmentioning
confidence: 53%
“…The kinetic data suggested that the active site of fucosidases might have some differences. However, the only available structures of α‐ l ‐fucosidase are from bacteria (Shaikh, Lammerts van Bueren, Davies, & Withers, ) and F. graminearum (Cao, Walton, Brumm, & Phillips, ). Although results obtained by molecular homology modeling are limited and they result in a less confident prediction, the comparison of α‐ l ‐fucosidase models from different animal species seems a faster route to identify the active site for this enzyme, which may be informative (Dolan, Noah, & Hurt, ; Nayeem, Sitkoff, & Krystek, ).…”
Section: Discussionmentioning
confidence: 99%